Association of COVID-19 incidence with objectively and subjectively measured mental health proxies in the Austrian Football League - an epidemiological study - van der Zee-Neuen, A.; Seymer, A.; Schaffler-Schaden, D.; Herfert, J.; O`Brien, J.; Johansson, T.; Kutschar, P.; Ludwig, S.; Stöggl, T.; Keeley, D.; Flamm, M.; Osterbrink, J. (All Life, 2021)
Objective: We aimed to explore the association of COVID-19 incidence with mental health in 225 team and staff members of five professional Austrian Football clubs captured by objective (location variance) or subjective (self-reported sleep quality, level of recovery, perceived risk of infection) mental health proxies.